Haemostatic Response of Polyethylene Terephthalate Treated by Oxygen and Nitrogen Plasma Afterglows - Metod Kolar; Gregor Primc (International Journal of Polymer Science)
Samples of polymer polyethylene terephthalate were coated with heparin and the haemostatic response has been determined by optical imaging of samples after incubation with fresh blood from a healthy donor. Prior to coating the samples were treated by neutral reactive particles of the oxygen or nitrogen plasma flowing afterglow. X-ray photoelectron spectroscopy analysis showed intensive functionalization of the polymer foils upon treatment with afterglows; however, the concentration of sulphur from heparin remained below the detection limit. The optical imaging showed densely distributed blood platelets in highly activated forms on untreated samples, whereas treatment with both afterglows revealed improved hemocompatibility. Best results were obtained for oxygen-functionalized polymer, whereas additional coating with heparin caused moderate loss of hemocompatibility, that was explained by deactivation of surface functional groups upon incubation with heparin.